PENGARUH STIMULASI DENGAN MENGGUNAKAN FLASH CARD TERHADAP PERKEMBANGAN BICARA DAN BAHASA ANAK USIA 48-72 BULAN DI TAMAN KANAK-KANAK PERBA CERIA KOTA KEDIRI - yuwantiwi, heni; 123, suwoyo; rahayu, dwi estuningq (Universitas Nusantara PGRI Kediri, 2019)
Early childhood is a child in the age range 0-6 years. Early childhood learns in their own way. The purpose of this study is to determine the effect of stimulation by using flash cards on the development of children aged 48-72 months in the Perba Ceria Kindergarten in the City of Kediri. This research method is survey experimental designwith the design of one group pretest and posttest design. The population is 35 children aged 48-72 months, a sample of 32. Sampling with simple random sampling. Data collection instruments using KPSP sheets aged 48-72 months andmedia flashcard. The results of the study using theformula wilxocon match paired test test shows that there is an effect of the value (Z count> Z table), the calculated Z value is -4.396, because the result of the calculation of wilxocon match paired test is an absolute price then the price (-) is not taken into account. Price of Z table with a significance level (ɑ) 0.05 of 1.645. So Ho is rejected and Ha is accepted. It can be concluded that there is an effect of stimulation by using flash cards on speech and language development of children aged 48-72 months in Perba Ceria kindergarten in Kediri City. Based on the results of the research above,media should flashcard be considered for teachers and parents to be used as a stimulation media for children.